Enhanced Physiochemical and Mechanical Performance of Chitosan‐Grafted Graphene Oxide for Superior Osteoinductivity. (28th December 2015) - Ruan, Jing; Wang, Xiansong; Yu, Zhang; Wang, Zi; Xie, Qing; Zhang, Dandan; Huang, Yazhuo; Zhou, Huifang; Bi, Xiaoping; Xiao, Caiwen; Gu, Ping; Fan, Xianqun
Abstract : The regeneration of artificial bone substitutes is a potential strategy for repairing bone defects. However, the development of substitutes with appropriate osteoinductivity and physiochemical properties, such as water uptake and retention, mechanical properties, and biodegradation, remains challenging. Therefore, there is a motivation to develop new synthetic grafts that possess good biocompatibility, physiochemical properties, and osteoinductivity. Here, we fabricate a biocompatible scaffold through the covalent crosslinking of graphene oxide (GO) and carboxymethyl chitosan (CMC). The resulting GO‐CMC scaffold shows significant high water retention (44% water loss) compared with unmodified CMC scaffolds (120% water loss) due to a steric hindrance effect. The modulus and hardness of the GO‐CMC scaffold are 2.75‐ and 3.51‐fold higher, respectively, than those of the CMC scaffold. Furthermore, the osteoinductivity of the GO‐CMC scaffold is enhanced due to the π–π stacking interactions of the GO sheets, which result in striking upregulation of osteogenesis‐related genes, including osteopontin, bone sialoprotein, osterix, osteocalcin, and alkaline phosphatase. Finally, the GO‐CMC scaffold exhibits excellent reparative effects in repairing rat calvarial defects via the synergistic effects of GO and bone morphogenetic protein‐2. This study provides new insights for developing bone substitutes for tissue engineering and regenerative medicine. Abstract : A biocompatible scaffold is fabricated through covalent crosslinking of graphene oxide (GO) and carboxymethyl chitosan (CMC). The steric hindrance effect of the network structure can improve the physiochemical and mechanical performance of the scaffold. The π–π stacking interactions between the aromatic rings in the inducer molecules and the GO basal plane can enhance the osteogenic differentiation of seed cells.